CRITERIA ANALISIS IN THE MODERN OERATING SYSTEMS IN THE TASKS OF PROTECTION OF INFORMATION RESOURCES - Юдін, О.; Весельська, О. (Science-based technologies, 2012)
Criteria, which give the completest information about the operating system from point of reliability, safety, comfort, productivity are developed. On the basis  of the developed critera the comparative analisys of the operating systems was conducted for the work stations of enterprises and estabilishments of different patterns of ownership. Among the operating systems which was subject comparson: Mac OS, Linux OS, Windows OS.